Contribution to the Research and Failure Analysis of the Geroler Hydraulic Motor - Osmanović, Almir; Lovrec, Darko; Halilović, Jasmin; Ćosić, Salko (International Conference Fluid Power 2025: Conference Proceedings, 2025)
This paper analyses the key aspects of the operation of geroler hydraulic motors, widely used rotary hydraulic motors. The focus is on understanding their performance, efficiency and durability in different working conditions. The work includes a theoretical analysis of the principles of work, supported by modelling. Furthermore, experimental tests conducted to characterize the motors in terms of torque, speed, flow and efficiency are considered. Special attention is paid to the analysis of factors that influence the wear of internal components. The results of the analysis provide deeper insight into the behaviour of geroler hydraulic motors, identify areas for potential improvements in design and application and for optimizing their operation and extending their service life in various industrial and mobile applications. In conclusion, the work contributes to a better understanding of hydraulic motors, which is crucial for engineers and technicians involved in the design, application and maintenance of hydraulic systems.